Effectiveness and cost-effectiveness of implementing HIV testing in primary care in East London: protocol for an interrupted time series analysis. Issue 12 (14th December 2017) - Leber, Werner; Beresford, Lee; Nightingale, Claire; Barbosa, Estela Capelas; Morris, Stephen; El-Shogri, Farah; McMullen, Heather; Boomla, Kambiz; Delpech, Valerie; Brown, Alison; Hutchinson, Jane; Apea, Vanessa; et al.
Abstract : Introduction: HIV remains underdiagnosed. Guidelines recommend routine HIV testing in primary care, but evidence on implementing testing is lacking. In a previous study, the Rapid HIV Assessment 2 (RHIVA2) cluster randomised controlled trial, we showed that providing training and rapid point-of-care HIV testing at general practice registration (RHIVA2 intervention) in Hackney led to cost-effective, increased and earlier diagnosis of HIV. However, interventions effective in a trial context may be less so when implemented in routine practice. We describe the protocol for an MRC phase IV implementation programme, evaluating the impact of rolling out the RHIVA2 intervention in a post-trial setting. We will use a longitudinal study to examine if the post-trial implementation in Hackney practices is effective and cost-effective, and a cross-sectional study to compare Hackney with two adjacent boroughs providing usual primary care (Newham) and an enhanced service promoting HIV testing in primary care (Tower Hamlets). Methods and analysis: Service evaluation using interrupted time series and cost-effectiveness analyses. We will include all general practices in three contiguous high HIV prevalence East London boroughs. All adults aged 16 and above registered with the practices will be included. The interventions to be examined are: a post-trial RHIVA2 implementation programme (including practice-based education and training, external quality assurance, incentive payments for rapid HIV testing and incorporation of rapid HIV testing in the sexual health Local Enhanced Service) in Hackney; the general practice sexual health Network Improved Service in Tower Hamlets and usual care in Newham. Coprimary outcomes are rates of HIV testing and new HIV diagnoses. Ethics and dissemination: The chair of the Camden and Islington NHS Research Ethics Committee, London, has endorsed this programme as an evaluation of routine care. Study results will be published in peer-reviewed journals and reported to commissioners.